Docking study, synthesis and antimicrobial evaluation of some novel 4-anilinoquinazoline derivatives - Rezvan Rezaee Nasab; Farshid Hassanzadeh; Ghadam Ali Khodarahmi; Mahboubeh Rostami; Mahmoud Mirzaei; Ali Jahanian-Najafabadi; Mahboubeh Mansourian (Wolters Kluwer Medknow Publications, 2017)
A series of novel 4-anilinoquinazoline derivatives were designed and synthesized from benzoic acid through ring closure, chlorination or nucleophilic substitution. The structures of compounds were characterized by IR, 1H-NMR and mass spectroscopy. All synthesized derivatives were screened for their antimicrobial activities against Gram-positive (Staphylococcus aurous, Bacillus subtilis, Listeria monocitogenes) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa, Salmonella entritidis) bacteria and also for antifungal activities against Candida albicans using the conventional micro dilution method. Most of the compounds have shown good antibacterial activities, especially compound 4c having highest activities against E. coli at 32 μg/mL concentration while the tested compounds did not exhibited remarkable antifungal activities. The potential DNA gyrase inhibitory activity of these compounds was investigated in silico using molecular docking simulation method. All compounds showed good results especially compound 4c which showed the lowest ΔGbind results (-8.16 Kcal/mol).